Pentingnya Evaluasi dalam Proses Pembelajaran dan Akibat Memanipulasinya - Magdalena, Ina; Hidayati, Nurul; Dewi, Ratri Hersita; Septiara, Sabgi Wulan; Maulida, Zahra (Lembaga Yasin AlSys, 2023)
Evaluation is an important activity carried out by educators in the learning process. By evaluating educators, they can improve their competence in class management both in choosing learning methods, media, teaching materials, and so on which can motivate students to learn. In addition, with evaluation educators can find out the level of success of their students. Therefore educators must carry out evaluation activities properly. However, in reality there are still many educators who have not carried out the evaluation process properly, especially in elementary schools. One of the causes is the lack of knowledge that educators have about the evaluation itself and it is often found that teachers manipulate student grades, as a result of manipulating grades will have a bad impact on their students. So that knowledge is needed about the concept, the role of evaluation to the procedures for carrying out evaluations in order to obtain evaluation results that can describe the real state of students.